Resin composition, circuit material containing same and printed circuit board

By designing a resin composition containing a specific resin and filler, the problems of insufficient dielectric constant stability and copper foil peel strength in the circuit materials in the prior art in high frequency applications are solved, and the circuit material performance of high dielectric constant, low dielectric loss and high peel strength are achieved.

CN119613830AActive Publication Date: 2025-03-14GUANGDONG SHENGYI SCI TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411921157.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-14
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

The prior art is difficult to provide circuit materials with high dielectric constant, low dielectric loss, high copper foil peel strength and dielectric constant stability, especially in high frequency applications.

Method used

By designing a resin composition, including a first thermosetting resin, a second thermosetting resin, a calcium titanate filler and amorphous molten silica filler, and controlling the proportion and purity of each component, a circuit material with excellent properties is prepared.

Benefits of technology

It realizes high dielectric constant, low dielectric loss, high copper foil peel strength and dielectric constant stability of circuit materials, and is suitable for the preparation of high-frequency substrates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005208034020000121
    Figure BDA0005208034020000121
  • Figure BDA0005208034020000131
    Figure BDA0005208034020000131
  • Figure BDA0005208034020000141
    Figure BDA0005208034020000141
Patent Text Reader

Abstract

The present invention provides a resin composition, a circuit material comprising the same, and a printed circuit board, the resin composition comprising (A) a first thermosetting resin comprising a polybutadiene resin and / or a polybutadiene copolymer resin having a number average molecular weight Mn < = 5000 g / mol; (B) a second thermosetting resin comprising polybutadiene resin and / or polybutadiene copolymer resin, the number average molecular weight Mn being greater than or equal to 15000 g / mol; (C) a first filler comprising calcium titanate, the particle size D50 of which is 6-10 [mu] m and the purity of which is greater than or equal to 99.5%; optionally (D) a second filler comprising amorphous fused silica, the particle size D50 of which is 8-12 [mu] m and the purity of which is greater than or equal to 99.5%; (E) a flame retardant; (F) a silane coupling agent; (G) a radical initiator; the circuit material prepared from the resin composition has the advantages of high dielectric constant, low dielectric loss, high copper foil peel strength, stable dielectric constant and good thickness consistency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electronic materials, and in particular relates to a resin composition, a circuit material containing the resin composition, and a printed circuit board. Background Art

[0002] In recent years, portable terminals such as smartphones are becoming popular. In addition, technological innovations such as IoT (Internet of Things) are also advancing. As a result, home appliances and electronic devices with wireless communication functions have been increasing. As a result, the amount of communication information in wireless networks has increased. In order to ensure communication speed and communication quality, the development of the fifth generation mobile communication system (abbreviated as 5G) is being promoted, and it has gradually been applied. In 5G, multiple antenna elements are used for high-level beamforming and spatial reuse, and in addition to the 6GHz frequency signals that have been used in the past, higher-frequency millimeter wave band signals such as tens of GHz are also used, so it can be expected that the communication speed will be increased and the communication quality will be improved. In 5G, the antenna module needs to be able to cope with high-frequency signals, and for this purpose, the dielectric loss tangent (Df) of the dielectric substrate is particularly required to be low in the high-frequency band.

[0003] Since high-frequency radio waves have high linearity, signals carried by high-frequency radio waves tend to be easily blocked by obstacles such as buildings. Therefore, in order to avoid this obstruction, multiple antenna devices are mounted on the antenna module. Since increasing the relative dielectric constant (Dk) of the substrate material can miniaturize the antenna device, increasing the relative dielectric constant (Dk) is effective for multiple mounting of antenna devices, and will also lead to the miniaturization of the antenna module, and then the miniaturization of the communication device. Therefore, the dielectric substrate used in the antenna module that can cope with high-frequency signals is required to have a relatively high dielectric constant (Dk) of a specified size, and the dielectric loss tangent (Df) is required to be low.

[0004] Microstrip antenna is a type of antenna successfully developed in the early 1970s. Due to its simple structure, low profile, light weight, conformal installation on the surface of the aircraft and integration with microstrip circuits, it has been widely used in the fields of communications and radar. However, since the microstrip antenna is a resonant structure, when it is applied to lower frequencies, its structural dimensions are usually large and cannot meet certain small size requirements. In recent years, the continuous development of wireless communication systems has put forward higher requirements for personal communication terminal modules. For example, as the role of GPS and Beidou systems in real life becomes increasingly significant, RF front-end modules are becoming increasingly portable: light, thin, short and small. Therefore, how to solve the problem of miniaturization of microstrip antennas has become one of the main research topics of microstrip antennas.

[0005] At present, the main methods for miniaturizing microstrip antennas include using special dielectric substrates, loading short-circuit probes, surface grooving, additional active networks, and using special microstrip patches. A common method is to use a high dielectric constant dielectric substrate to reduce the size of the microstrip antenna, but the main defect of this type of high dielectric constant dielectric antenna is that it excites strong surface waves, resulting in large surface losses, reduced gain, and reduced efficiency. In order to increase the gain, the antenna surface is often covered with a high dielectric constant dielectric, but this increases the thickness of the antenna.

[0006] According to the basic theory and design of microstrip antennas, selecting a dielectric substrate with a high dielectric constant (Dk) can reduce the size of the antenna. Covering the antenna surface with a high dielectric constant medium and increasing the thickness can increase the radiation efficiency and improve the antenna gain.

[0007] In antenna design, the stability and consistency of the dielectric constant and thickness of the dielectric substrate material are important indicators that affect the gain and other performance of the antenna. The thickness variation deviation of the dielectric substrate will cause the efficiency of the antenna to decrease. In antenna design, the deviation of the dielectric layer thickness is a factor that has a greater impact on the antenna performance than the stability of the dielectric constant. At the same time, the deviation of the thickness will also lead to different resin content, and different resin content will also directly affect the stability of the dielectric constant.

[0008] When manufacturing thick dielectric substrates, in order to ensure thickness uniformity, a large amount of fillers and resins with high molecular weight are used to increase the dielectric constant (Dk) and reduce glue flow. This will result in low copper foil peel strength of the dielectric substrate and even voids inside the dielectric substrate, further leading to poor stability of the dielectric constant of the dielectric substrate.

[0009] In summary, in order to cope with the high frequency of the antenna module, the dielectric loss tangent (Df) of the dielectric substrate must be low; in order to miniaturize the antenna module and then bring about the miniaturization of the communication device, the dielectric substrate must have a relatively high dielectric constant (Dk) of a specified size; the selection of a dielectric substrate with a high dielectric constant (Dk) can reduce the size of the antenna. To increase the gain, the thickness of the antenna must be increased, thereby increasing the thickness of the dielectric substrate; after the thickness of the dielectric substrate increases, the dielectric constant and thickness stability and consistency of the dielectric substrate material will face many challenges. In order to ensure thickness uniformity, a large amount of fillers and resins with high molecular weight will be used to increase the dielectric constant (Dk) and reduce glue flow, which will result in low copper foil peel strength of the dielectric substrate.

[0010] Therefore, how to provide a resin composition with excellent performance so that it can be used to prepare circuit materials with higher dielectric constant, lower dielectric loss, higher copper foil peel strength, stable dielectric constant and good thickness consistency has become a technical problem that needs to be solved urgently. Summary of the invention

[0011] In view of the deficiencies in the prior art, the object of the present invention is to provide a resin composition, a circuit material and a printed circuit board comprising the same. By designing the specific composition of the resin composition, a resin composition with excellent performance is prepared, and the circuit material prepared thereby has a higher dielectric constant, lower dielectric loss, higher copper foil peel strength, stable dielectric constant and good thickness consistency.

[0012] To achieve this object, the present invention adopts the following technical solutions:

[0013] In one aspect, the present invention provides a resin composition comprising the following components:

[0014] (A) a first thermosetting resin, comprising a polybutadiene resin and / or a polybutadiene copolymer resin, with a number average molecular weight Mn≤5000 g / mol;

[0015] (B) a second thermosetting resin, comprising a polybutadiene resin and / or a polybutadiene copolymer resin, with a number average molecular weight Mn ≥ 15000 g / mol;

[0016] (C) a first filler, comprising calcium titanate, having a particle size D50 of 6 to 10 μm and a purity of ≥99.5%;

[0017] Optional (D) second filler, comprising amorphous fused silica, with a particle size D50 of 8 to 12 μm and a purity of ≥99.5%;

[0018] (E) flame retardants;

[0019] (F) a silane coupling agent;

[0020] (G) Free radical initiator.

[0021] In the present invention, the first thermosetting resin polybutadiene resin and / or polybutadiene copolymer resin has a number average molecular weight Mn≤5000g / mol. The molecular weight of the first thermosetting resin is relatively low, mainly to provide flow glue and glass fiber cloth infiltration in the formula, and to improve the density of the board and the copper foil peeling strength. In the present invention, the number average molecular weight of the first thermosetting resin polybutadiene resin and / or polybutadiene copolymer resin can be 1000g / mol, 1400g / mol, 1800g / mol, 2200g / mol, 2600g / mol, 3000g / mol, 3500g / mol, 4000g / mol, 4500g / mol or 5000g / mol, etc. In the present invention, the second thermosetting resin is a polybutadiene resin and / or a polybutadiene copolymer resin, and the number average molecular weight Mn is ≥15000 g / mol. The molecular weight of the second thermosetting resin is relatively high, and the size of the glue flow is mainly adjusted in the formula. When the glue flow of the formula is large, it is necessary to increase the proportion of the second thermosetting resin to reduce the glue flow. When the glue flow of the formula is small, it is necessary to reduce the proportion of the second thermosetting resin to increase the glue flow. In the present invention, the number average molecular weight of the second thermosetting resin polybutadiene resin and / or polybutadiene copolymer resin can be 15000 g / mol, 16000 g / mol, 17000 g / mol, 18000 g / mol, 19000 g / mol, 20000 g / mol, 22000 g / mol, 24000 g / mol, 25000 g / mol, 30000 g / mol, 40000 g / mol, 50000 g / mol, 60000 g / mol, 65000 g / mol, 70000 g / mol, 80000 g / mol, 90000 g / mol, 100000 g / mol, 110000 g / mol or 120000 g / mol, etc.

[0022] In the present invention, the first filler calcium titanate has a particle size D50 of 6 to 10 μm and a purity of ≥99.5%. Calcium titanate is a cubic crystal system and a typical representative of the perovskite structure. Due to its structural characteristics, the interaction of titanium ions in the titanium oxide octahedron in the perovskite lattice structure produces a large internal electric field, which makes it have a higher relative dielectric constant of 150 to 160. Therefore, in order to further improve the dielectric constant of the dielectric substrate, the effect of using calcium titanate to improve the dielectric constant is more obvious.

[0023] In the present invention, the median particle size D50 of the calcium titanate filler can be 6μm, 7μm, 8μm, 9μm or 10μm. If the particle size D50 of calcium titanate is less than 6μm, the oil absorption value of the filler is high, and the viscosity of the glue is too high, which affects the processability of the glue application, resulting in uneven thickness of the sheet, and also leads to small glue flow of the sheet, resulting in low peel strength of the copper foil; if the particle size D50 of calcium titanate is greater than 10μm, the density of calcium titanate (4.1g / cm 3 ) is large and easy to settle, and the filler is unevenly dispersed, which ultimately leads to unstable dielectric constant and poor consistency of the dielectric substrate. It will also cause the formation of board edge grooves due to large glue flow when the thick board is pressed, resulting in uneven board thickness, which will also lead to unstable dielectric constant and poor consistency. Especially when the thickness required by the customer is very thick, such as 30mil (0.762mm), 40mil (1.016mm), 80mil (2.032mm), 160mil (4.064mm), 240mil (6.096mm), the control of the thickness consistency of the whole board is more critical.

[0024] In the present invention, the inventors have found through a large number of experimental studies that the purity of calcium titanate will affect the dielectric loss of the dielectric substrate, especially when the proportion of calcium titanate in the formula is high, the effect on the dielectric loss of the dielectric substrate is more obvious. When the purity is ≥99.5%, the soluble conductive substances or impurities in the filler are relatively less, so that the dielectric loss of the dielectric substrate will be relatively small. In order to further control the dielectric loss of the dielectric substrate, it is further preferred that the conductivity of calcium titanate is ≤10μS / cm, for example, it can be 10μS / cm, 9μS / cm, 8μS / cm, 7μS / cm, 6μS / cm, 5μS / cm, 4μS / cm, 3μS / cm, 2μS / cm, 1μS / cm, etc.

[0025] In the present invention, the optional (D) second filler means that the resin composition may or may not contain the second filler.

[0026] In the present invention, the second filler is amorphous fused silica, with a particle size D50 of 8 to 12 μm and a purity of ≥99.5%. The dielectric constant of amorphous fused silica is 3.6 to 3.8, and the main function of amorphous fused silica in the formula is to adjust the dielectric constant of the dielectric substrate. When the dielectric constant Dk of the dielectric substrate is ≥10, the addition ratio of calcium titanate in the formula is relatively high, and amorphous fused silica can be added without or at a relatively low ratio as needed. In the present invention, the median particle size D50 of the amorphous fused silica filler can be 8 μm, 9 μm, 10 μm, 11 μm or 12 μm, etc. In the present invention, the inventors have found through a large number of experimental studies that when the resin formula of the present invention is used, if the particle size D50 of amorphous fused silica is less than 8μm, when it is used in combination with calcium titanate with a relatively high addition ratio, the viscosity of the glue solution increases, which affects the glue application process, and the filler has a large oil absorption value, and the substrate is prone to produce voids, resulting in poor dielectric constant stability of the dielectric substrate, and also reducing the copper foil peeling strength of the plate. If the particle size D50 of amorphous fused silica is greater than 12μm, the glue flow will be large when pressing the plate, especially when pressing thick plates, it is easy to produce gullies, resulting in poor thickness consistency of the dielectric substrate. In order to obtain lower dielectric loss, the purity of the amorphous fused silica used is ≥99.5%. In order to further obtain lower dielectric loss, the conductivity of the amorphous fused silica is preferably ≤10μS / cm, for example, it can be 10μS / cm, 9μS / cm, 8μS / cm, 7μS / cm, 6μS / cm, 5μS / cm, 4μS / cm, 3μS / cm, 2μS / cm, 1μS / cm, etc.

[0027] In the present invention, based on 100 parts by weight of the resin composition, the sum of the parts by weight of components (A) and (B) is 18 to 25 parts by weight (e.g., 18, 19, 20, 22, 24 or 25 parts, etc.), the amount of component (C) is 60 to 70 parts by weight (e.g., 60, 62, 64, 65, 66, 67, 68 or 70 parts, etc.), and the amount of component (D) is 0 to 15 parts by weight (e.g., 0, 0.5, 1 If the sum of the contents of the resin (components (A) and (B)) is too little, the resin will not be able to fill the gaps between the fillers, and voids will easily form, resulting in voids in the board and low peel strength. The voids will also lead to poor consistency in thickness and dielectric constant of the entire board. If the sum of the contents of components (A) and (B) is too high, excessive glue flow will occur, affecting the consistency of the thickness of the board and the consistency of the dielectric constant of the entire board. The dielectric constant of component (C) calcium titanate is relatively high, with a dielectric constant of 150 to 160, while the dielectric constant of component (D) amorphous fused silica is relatively low, with a dielectric constant of 3.6 to 3.8. By adjusting the addition amounts of components (C) and (D), different dielectric constants of the dielectric substrate Dk ≥ 10 can be achieved.

[0028] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.

[0029] As a preferred technical solution of the present invention, the mass ratio of component (A) to component (B) is 1:(0.5-2), for example, it can be 1:0.5, 1:0.8, 1:1, 1:1.2, 1:1.4, 1:1.6, 1:1.8 or 1:2, etc.

[0030] Because the first thermosetting resin component (A) polybutadiene resin and / or polybutadiene copolymer resin (number average molecular weight Mn ≤ 5000g / mol) has a small molecular weight, it will flow when heated and pressurized when used alone, and it is easy to produce surface defects such as gullies. In addition, the thickness at the edge of the board is thin, and the thickness of the entire board is unstable, which will lead to poor consistency of the dielectric constant of the entire board. In order to ensure that the high-frequency substrate has good thickness consistency and dielectric constant consistency of the entire board, in the present invention, the second thermosetting resin component (B) polybutadiene resin and / or polybutadiene copolymer resin (number average molecular weight Mn ≥ 15000g / mol) is added to the formula to ensure that the high-frequency substrate has good thickness consistency and dielectric constant consistency of the entire board. The best effect is achieved when the mass ratio of component (A) to component (B) is 1:(0.5-2). If the proportion of component (B) is too low, the purpose of improving thickness consistency and dielectric constant consistency of the entire board cannot be achieved. If the proportion of component (B) is too high, glue flow is likely to occur, resulting in voids in the board and low peel strength. Voids will also lead to poor thickness consistency and dielectric constant consistency of the entire board.

[0031] As a preferred technical solution of the present invention, the polybutadiene resin is selected from any one or a combination of at least two of 1,2-polybutadiene resin, maleic anhydride-modified polybutadiene resin, acrylate-modified polybutadiene resin, epoxy-modified polybutadiene resin, amine-modified polybutadiene resin, terminal carboxyl-modified polybutadiene resin or terminal hydroxyl-modified polybutadiene resin;

[0032] As a preferred technical solution of the present invention, the polybutadiene copolymer resin is selected from any one of polybutadiene-styrene copolymer resin, styrene-butadiene-styrene copolymer resin, styrene-(ethylene-butylene)-styrene copolymer resin, polybutadiene-styrene-divinylbenzene graft copolymer resin, maleic anhydride modified styrene-butadiene copolymer resin or acrylate modified styrene-butadiene copolymer resin or a combination of at least two thereof.

[0033] As a preferred technical solution of the present invention, based on 100 parts by weight of the resin composition, the weight of the flame retardant is 5 to 15 parts, for example, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts or 15 parts, etc.

[0034] Preferably, the flame retardant comprises a bromine-containing flame retardant and / or a phosphorus-containing flame retardant.

[0035] Preferably, the bromine-containing flame retardant is selected from any one of decabromodiphenyl ether, decabromodiphenyl ethane or ethylenebistetrabromophthalimide or a combination of at least two thereof.

[0036] Preferably, the phosphorus-containing flame retardant is selected from any one of tri(2,6-dimethylphenyl)phosphine, 10-(2,5-dihydroxyphenyl)-9,10-dihydro-9-oxa-10-phosphophananthen-10-oxide, 2,6-bis(2,6-dimethylphenyl)phosphinobenzene or 10-phenyl-9,10-dihydro-9-oxa-10-phosphophananthen-10-oxide, or a combination of at least two thereof.

[0037] As a preferred technical solution of the present invention, the silane coupling agent is a vinyl silane coupling agent.

[0038] Based on 100 parts by weight of the resin composition, the weight of the silane coupling agent is 0.1 to 1 part, for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1 part.

[0039] In the present invention, the free radical initiator is a carbon-based free radical initiator or a composite free radical initiator.

[0040] As a preferred technical solution of the present invention, based on 100 parts by weight of the resin composition, the weight of the free radical initiator is 0.1 to 1 part, for example, it can be 0.1 part, 0.2 part, 0.3 part, 0.4 part, 0.5 part, 0.6 part, 0.7 part, 0.8 part, 0.9 part or 1 part, etc.

[0041] Preferably, the composite free radical initiator comprises a combination of at least one organic peroxide free radical initiator and at least one carbon-based free radical initiator.

[0042] Preferably, the organic peroxide free radical initiator is selected from any one of diisopropylbenzene peroxide, 1,3-bis(tert-butylperoxyisopropyl)benzene, 2,5-di-tert-butylperoxy-2,5-dimethylhexane, 2,5-di-tert-butylperoxy-2,5-dimethylhexyne-3, di-tert-butyl peroxide or tert-butylperoxide isopropylbenzene, or a combination of at least two thereof.

[0043] Preferably, the carbon-based free radical initiator is selected from any one of 2,3-dimethyl-2,3-diphenylbutane, 2,3-dimethyl-2,3-di(4-methylphenyl)butane, 2,3-dimethyl-2,3-di(4-isopropylphenyl)butane, and 3,4-dimethyl-3,4-diphenylhexane, or a combination of at least two thereof.

[0044] It should be noted that the resin composition of the present invention can also be used in combination with various other polymers, as long as they do not damage the inherent properties of the resin composition. The various other polymers exemplarily include but are not limited to: liquid crystal polymers, thermoplastic resins, different flame retardant compounds or additives, etc.; and can be used alone or in combination as needed.

[0045] It should also be noted that the present invention does not impose any special restrictions on the preparation method of the resin composition, and all commonly used preparation methods in the art are applicable, including but not limited to: stirring and mixing all components of the resin composition to obtain the resin composition.

[0046] In the present invention, the filler particle size test method is to use Malvern 3000 laser particle size analyzer for testing; the number average molecular weight Mn of the thermosetting resin is tested according to GB / T 21863-2008, and is measured by gel permeation chromatography based on polystyrene calibration; the filler purity test method is to use inductively coupled plasma emission spectrometry (ICP) for testing, and by measuring the unique spectral line and intensity of each element and comparing it with the standard solution, the type and content of the element contained in the sample can be known; the filler conductivity test method adopts a mixed liquid method, and the mixed liquid method uses a conductivity meter to measure the conductivity of the mixed liquid, and then calculates the filler conductivity according to the pH value and solute concentration.

[0047] In a second aspect, the present invention provides a dielectric substrate, comprising a reinforcing material and the resin composition according to the first aspect coated on the reinforcing material.

[0048] As a preferred technical solution of the present invention, the reinforcing material is electronic grade glass fiber cloth.

[0049] Preferably, the reinforcing material is glass fiber cloth surface-treated with a vinyl silane coupling agent.

[0050] In a third aspect, the present invention provides a circuit material, comprising the dielectric substrate layer as described in the second aspect and a conductive metal layer stacked on one side or both sides of the dielectric substrate layer;

[0051] Preferably, the conductive metal layer is copper foil.

[0052] Preferably, the copper foil has a thickness of 9 to 150 μm, for example, 9 μm, 20 μm, 30 μm, 40 μm, 50 μm, 70 μm, 90 μm, 110 μm, 120 μm, 130 μm, 140 μm or 150 μm.

[0053] The present invention uses the resin composition to ensure that the circuit material prepared from the resin composition has a dielectric constant Dk≥10 and a dielectric loss Df≤0.0030 at a frequency of 10 GHz.

[0054] It should be noted that there is no specific limitation on the method for preparing the circuit material in the present invention. Exemplarily, the method for preparing the circuit material comprises the following steps:

[0055] (1) dissolving or dispersing a resin composition in a solvent to obtain a resin glue solution, impregnating a reinforcing material with the resin glue solution, and then drying and removing the solvent to obtain a prepreg;

[0056] (2) At least one prepreg is stacked together, a conductive metal layer is provided on one or both sides of the surface, and then placed in a laminator and cured by heat pressing to obtain the circuit material.

[0057] It should be noted that the present invention has no special restrictions on the solvent in step (1), and organic solvents commonly used in the art are applicable, including but not limited to: alcohols such as methanol, ethanol, and butanol, ethers such as ethyl cellosolve, butyl cellosolve, ethylene glycol-methyl ether, diethylene glycol ethyl ether, and diethylene glycol butyl ether, ketones such as acetone, butanone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone, aromatic hydrocarbons such as toluene, xylene, and mesitylene, esters such as ethoxyethyl acetate and ethyl acetate, nitrogen-containing solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone. The above solvents can be used alone or in combination of two or more.

[0058] Based on 100 parts by weight of the resin composition, the weight of the solvent is 40 to 120 parts, for example, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 105, 110, 115 or 120 parts, etc.

[0059] In a fourth aspect, the present invention provides a printed circuit board, wherein the printed circuit board comprises the dielectric substrate as described in the second aspect and / or the circuit material as described in the third aspect.

[0060] Preferably, the printed circuit board is a high-frequency substrate.

[0061] In the present invention, high-frequency substrate refers to a special circuit board with a higher radio frequency, and is specifically defined as a substrate with a frequency above 1 GHz.

[0062] Compared with the prior art, the present invention has the following beneficial effects:

[0063] (1) The present invention designs the specific composition of the resin composition, further compounding with a calcium titanate filler having a median particle size D50 of 6 to 10 μm and an amorphous fused silica filler having a median particle size D50 of 8 to 12 μm, and controlling the content of the thermosetting resin within a specific range. The circuit material prepared has a higher dielectric constant, lower dielectric loss, higher copper foil peel strength, stable dielectric constant and good thickness consistency, and is suitable for preparing high-frequency substrates.

[0064] (2) The present invention compounded a first thermosetting resin polybutadiene resin and / or polybutadiene copolymer resin (number average molecular weight Mn≤5000 g / mol) with a second thermosetting resin polybutadiene resin and / or polybutadiene copolymer resin (number average molecular weight Mn≥15000 g / mol), and controlled the addition amounts of the two, thereby ensuring that the high-frequency substrate has good thickness consistency and dielectric constant consistency of the whole board, and the peel strength of the board is high.

[0065] (3) The present invention controls the purity of calcium titanate and amorphous fused silica to be ≥99.5%, which is the key to ensuring that the circuit material has a lower dielectric loss and ensures that the dielectric loss Df of the dielectric substrate is ≤0.0030. DETAILED DESCRIPTION

[0066] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0067] The sources of some components in the examples and comparative examples are shown in Table 1 below.

[0068] Table 1

[0069]

[0070] Embodiment 1-11

[0071] Embodiments 1-11 provide a circuit material and a preparation method thereof, respectively, wherein the circuit material comprises a dielectric substrate layer, a conductive metal layer, and conductive metal layers on both sides of the dielectric substrate layer;

[0072] The dielectric substrate layer includes a reinforcing material and a resin composition coated on the reinforcing material. The specific composition of the resin composition and the specific composition materials of the circuit material are shown in Table 2 below. The dosage units of the resin composition in Table 2 are all parts by weight, the unit of the reinforcing material is the number of sheets, and the unit of the conductive metal layer is the number of sheets.

[0073] The preparation method of the above circuit material is as follows:

[0074] (1) dissolving or dispersing the resin composition in xylene to obtain a resin glue solution (solid content 65%), impregnating the reinforcing material with the resin glue solution, drying and removing the solvent to obtain a bonding sheet;

[0075] (2) Take 6 adhesive sheets, press a copper foil on each side of them, and place them in a laminator at a temperature of 245°C and a pressure of 60 kg / cm 2 The circuit material is then cured by heat pressing to obtain the circuit material.

[0076] Comparative Examples 1-6

[0077] Comparative Examples 1-6 respectively provide a circuit material and a preparation method thereof. The specific composition of the resin composition and the specific constituent materials of the circuit material are shown in Table 3 below. The dosage units of the resin composition in Table 3 are all parts by weight.

[0078] The circuit materials described in Comparative Examples 1-6 can be prepared by the preparation methods provided in the above embodiments.

[0079] Table 2

[0080]

[0081]

[0082] Table 3

[0083]

[0084] The performance of the circuit materials (boards) provided in the above embodiments and comparative examples was tested, and the specific testing method is as follows:

[0085] (1) Dielectric constant (Dk) and dielectric loss (Df): The dielectric constant (Dk) and dielectric loss (Df) of the board are tested using the SPDR method at a frequency of 10 GHz.

[0086] (2) Peel strength (PS): According to the "after thermal stress" experimental conditions in IPC-TM-650 2.4.8 method, the peel strength of the sheet is tested. The unit of peel strength is N / mm.

[0087] (3) Thickness consistency: Take five samples at the four corners and the middle of the plate to test the thickness of the plate. If the thickness of the plate meets the third-level tolerance of the copper clad laminate, the thickness consistency is good. If the thickness of the plate does not meet the third-level tolerance of the copper clad laminate, the thickness consistency is poor.

[0088] (4) Dk consistency: Take five samples at the four corners and the middle of the plate to test the Dk of the plate. If the Dk range of the plate is less than or equal to 0.05, the Dk consistency is good. If the Dk range of the plate is greater than 0.05, the Dk consistency is poor.

[0089] The above performance test results are detailed in Table 3 below.

[0090] Table 3

[0091] Dk(10GHz) Df(10GHz) Peel strength Thickness consistency Dk consistency Example 1 10.0 0.0026 0.82 good good Example 2 11.6 0.0027 0.83 good good Example 3 13.5 0.0028 0.75 good good Example 4 10.5 0.0027 0.72 good good Example 5 10.6 0.0027 0.73 good good Example 6 12.2 0.0029 0.74 good good Example 7 10.2 0.0028 0.81 Difference Difference Example 8 10.1 0.0028 0.53 good good Comparative Example 1 10.1 0.0027 0.81 Difference Difference Comparative Example 2 10.0 0.0028 0.52 good Difference Comparative Example 3 10.2 0.0027 0.79 Difference Difference Comparative Example 4 10.0 0.0028 0.56 good Difference Comparative Example 5 10.1 0.0027 0.81 Difference Difference Comparative Example 6 13.6 0.0039 0.76 good good Comparative Example 7 10.8 0.0035 0.78 good good Comparative Example 8 9.6 0.0026 0.77 Difference Difference Comparative Example 9 13.8 0.0029 0.49 Difference Difference

[0092] From the above content, it can be seen that in the present invention, by designing the specific composition of the resin composition, further compounding by using a calcium titanate filler with a median particle size D50 of 6 to 10 μm and an amorphous fused silica filler with a median particle size D50 of 8 to 12 μm, and controlling the content of the thermosetting resin within a specific range, the prepared circuit material has a higher dielectric constant, lower dielectric loss, higher copper foil peel strength, stable dielectric constant and good thickness consistency, and is suitable for preparing high-frequency substrates, wherein the dielectric constant (Dk, 10 GHz) is ≥10, the dielectric loss (Df, 10 GHz) is ≤0.003, the peel strength (PS) is 0.72 to 0.83 N / mm, the thickness consistency is good, and the Dk consistency is good.

[0093] From the comparison of the data of Examples 1-6 and Examples 7-8, it can be seen that in the present invention, by controlling the mass ratio of the first thermosetting resin polybutadiene resin and / or polybutadiene copolymer resin (number average molecular weight Mn≤5000 g / mol) to the second thermosetting resin polybutadiene resin and / or polybutadiene copolymer resin (number average molecular weight Mn≥15000 g / mol) within a specific range, the performance of the resin composition is further improved, and a circuit material with excellent performance is prepared.

[0094] From the comparison between Example 1 and Comparative Example 1, it can be seen that when the number average molecular weight Mn of the second thermosetting resin polybutadiene resin and / or polybutadiene copolymer resin is less than 15000 g / mol, the glue is likely to flow and produce grooves during plate pressing, resulting in poor thickness consistency of the plate, and the poor thickness consistency further leads to poor Dk consistency of the plate.

[0095] From the comparison between Example 1 and Comparative Examples 2 and 4, it can be seen that when the particle size of calcium titanate and the particle size of amorphous fused silica are small, the oil absorption value of the filler is high, and voids are easily generated in the substrate, resulting in poor stability of the dielectric constant of the dielectric substrate and reducing the copper foil peeling strength of the board.

[0096] From the comparison between Example 1 and Comparative Examples 3 and 5, it can be seen that when the particle size of calcium titanate and the particle size of amorphous fused silica are large, the glue flow will be larger when pressing the plate, especially when pressing thick plates, it is easy to produce grooves, resulting in poor thickness consistency of the dielectric substrate, and poor thickness consistency further leads to poor Dk consistency of the plate.

[0097] From the comparison between Example 3 and Comparative Example 6, and Example 5 and Comparative Example 7, it can be seen that when the purity of calcium titanate and amorphous fused silica is lower than 99.5%, the dielectric loss (Df, 10 GHz) of the dielectric substrate will be greater than 0.003.

[0098] From the comparison between Example 1 and Comparative Example 8, it can be seen that when the addition ratio of the first thermosetting resin polybutadiene resin and / or polybutadiene copolymer resin (number average molecular weight Mn≤5000g / mol) and the second thermosetting resin polybutadiene resin and / or polybutadiene copolymer resin (number average molecular weight Mn≥15000g / mol) is too high, it will cause excessive glue flow, affecting the thickness consistency of the board and the dielectric constant consistency of the entire board.

[0099] From the comparison between Example 1 and Comparative Example 9, it can be seen that when the addition ratio of the first thermosetting resin polybutadiene resin and / or polybutadiene copolymer resin (number average molecular weight Mn≤5000g / mol) to the second thermosetting resin polybutadiene resin and / or polybutadiene copolymer resin (number average molecular weight Mn≥15000g / mol) is too small, the resin cannot fill the gaps between the fillers and easily forms voids, resulting in voids in the board and low peel strength. The voids will also lead to poor thickness consistency and dielectric constant consistency of the entire board.

[0100] In summary, in the present invention, a resin composition with excellent performance is prepared by designing the specific composition of the resin composition. The circuit material prepared from the resin composition has a high dielectric constant, low dielectric loss, high copper foil peel strength, a stable dielectric constant and good thickness consistency.

[0101] The applicant declares that the present invention uses the above embodiments to illustrate the resin composition, circuit material and printed circuit board containing the same, but the present invention is not limited to the above embodiments, that is, it does not mean that the present invention must rely on the above embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A resin composition, characterized in that The resin composition comprises the following components: (A) a first thermosetting resin, comprising a polybutadiene resin and / or a polybutadiene copolymer resin, with a number average molecular weight Mn≤5000 g / mol; (B) a second thermosetting resin, comprising a polybutadiene resin and / or a polybutadiene copolymer resin, with a number average molecular weight Mn ≥ 15000 g / mol; (C) a first filler, comprising calcium titanate, having a particle size D50 of 6 to 10 μm and a purity of ≥99.5%; Optional (D) second filler, comprising amorphous fused silica, with a particle size D50 of 8 to 12 μm and a purity of ≥99.5%; (E) flame retardants; (F) a silane coupling agent; (G) Free radical initiator.

2. The resin composition according to claim 1, characterized in that Based on 100 parts by weight of the resin composition, the sum of the parts by weight of components (A) and (B) is 18 to 25 parts by weight; Preferably, based on 100 parts by weight of the resin composition, the amount of component (C) is 60 to 70 parts by weight; Preferably, based on 100 parts by weight of the resin composition, the amount of component (D) is 0 to 15 parts by weight.

3. The resin composition according to claim 1 or 2, characterized in that The mass ratio of the component (A) to the component (B) is 1:(0.5-2).

4. The resin composition according to any one of claims 1 to 3, characterized in that The polybutadiene resin is selected from any one or a combination of at least two of 1,2-polybutadiene resin, maleic anhydride-modified polybutadiene resin, acrylate-modified polybutadiene resin, epoxy-modified polybutadiene resin, amine-modified polybutadiene resin, terminal carboxyl-modified polybutadiene resin or terminal hydroxyl-modified polybutadiene resin; Preferably, the polybutadiene copolymer resin is selected from any one of polybutadiene-styrene copolymer resin, styrene-butadiene-styrene copolymer resin, styrene-(ethylene-butylene)-styrene copolymer resin, polybutadiene-styrene-divinylbenzene graft copolymer resin, maleic anhydride modified styrene-butadiene copolymer resin or acrylate modified styrene-butadiene copolymer resin or a combination of at least two thereof.

5. The resin composition according to any one of claims 1 to 4, characterized in that The conductivity of the calcium titanate is ≤10 μS / cm; Preferably, the electrical conductivity of the amorphous fused silica is ≤10 μS / cm.

6. The resin composition according to any one of claims 1 to 5, characterized in that Based on 100 parts by weight of the resin composition, the weight of the flame retardant is 5 to 15 parts; Preferably, the flame retardant comprises a bromine-containing flame retardant and / or a phosphorus-containing flame retardant; Preferably, the flame retardant comprises a bromine-containing flame retardant and / or a phosphorus-containing flame retardant; Preferably, the bromine-containing flame retardant is selected from any one or a combination of at least two of decabromodiphenyl ether, decabromodiphenyl ethane or ethylenebistetrabromophthalimide; Preferably, the phosphorus-containing flame retardant is selected from any one of tri(2,6-dimethylphenyl)phosphine, 10-(2,5-dihydroxyphenyl)-9,10-dihydro-9-oxa-10-phosphophananthen-10-oxide, 2,6-bis(2,6-dimethylphenyl)phosphinobenzene or 10-phenyl-9,10-dihydro-9-oxa-10-phosphophananthen-10-oxide, or a combination of at least two thereof.

7. The resin composition according to any one of claims 1 to 6, characterized in that The silane coupling agent is a vinyl silane coupling agent; Preferably, based on 100 parts by weight of the resin composition, the weight portion of the silane coupling agent is 0.1 to 1 part; Preferably, the free radical initiator is a carbon-based free radical initiator or a composite free radical initiator; Preferably, based on 100 parts by weight of the resin composition, the weight portion of the free radical initiator is 0.1 to 1 part; Preferably, the composite free radical initiator comprises a combination of at least one organic peroxide free radical initiator and at least one carbon-based free radical initiator; Preferably, the organic peroxide free radical initiator is selected from any one of diisopropylbenzene peroxide, 1,3-bis(tert-butylperoxyisopropyl)benzene, 2,5-di-tert-butylperoxy-2,5-dimethylhexane, 2,5-di-tert-butylperoxy-2,5-dimethylhexyne-3, di-tert-butyl peroxide or tert-butylperoxide isopropylbenzene, or a combination of at least two thereof; Preferably, the carbon-based free radical initiator is selected from any one of 2,3-dimethyl-2,3-diphenylbutane, 2,3-dimethyl-2,3-di(4-methylphenyl)butane, 2,3-dimethyl-2,3-di(4-isopropylphenyl)butane, and 3,4-dimethyl-3,4-diphenylhexane, or a combination of at least two thereof.

8. A dielectric substrate, characterized in that: The dielectric substrate comprises a reinforcing material and a resin composition according to any one of claims 1 to 7 coated on the reinforcing material; Preferably, the reinforcing material is electronic grade glass fiber cloth; Preferably, the reinforcing material is glass fiber cloth surface-treated with a vinyl silane coupling agent.

9. A circuit material, characterized in that: The circuit material comprises the dielectric substrate layer as claimed in claim 8 and a conductive metal layer stacked on one side or both sides of the dielectric substrate layer; Preferably, the conductive metal layer is copper foil.

10. A printed circuit board, characterized in that: The printed circuit board comprises the dielectric substrate as claimed in claim 8 and / or the circuit material as claimed in claim 9; Preferably, the printed circuit board is a high-frequency substrate.

Citation Information

Patent Citations

  • Circuit material and printed circuit board

    CN115847952A

  • Resin composition, circuit material containing same and printed circuit board

    CN117924812A

  • Thermosetting resin composition, prepreg, resin film, laminate, printed wiring board, antenna device, antenna module, and communication device

    CN118541450A

  • Thermosetting resin composition and printed circuit board including the same

    US20200325304A1